Herbaceous biomass production in the establishment of an agriculturecattle rearing-forest integration system with two alternatives for weeds control - Mota, Veronica A.; Santos, L. D. T.; Alfonso, Jatnel; Santos Junior, A.; Machado, V. D.; Santos, M. V.; Leite, G. L. D. (Cuban Journal of Agricultural Science, 2011)
The productive performance of an agriculture-cattle rearing-forest integration system (ILPF)1 , formed by intercropping sorghum and three forage grasses (Andropogon gayanus, Panicum maximum cv. Tanzania, and Brachiaria brizantha cv. Xara?s) was studied and managed with two variants of weeds control at the Northern region of Minas Gerais. A random block design was used with factorial fit (3 x 2) and four replicates. Before the sorghum collection for forage, 90 d after the sowing, plant height, number of plants, and dry matter yield were measured in sorghum and the forage plants. Later, 290 d after the sowing, the dry matter of the weeds, the sprouts of sorghum, and the forage plants were estimated again. Also, the intercropping efficiency was determined through the calculation of the index of equivalence of the area, partial and total. The factors under study, intercropping of forage plants and weeds management, did not show interaction (P > 0.05) in the indicators. The atrazine application did not affect the sorghum production or the pastures establishment. In the monoculture, the production of A. gayanus cv. Planaltina was 11.24 % lower than that recorded in the intercropping of B. brizantha cv. Xara?s and P. maximum cv. Tanzania, which produced 505.03 and 134.64 % more than in the monoculture. The index of equivalence of the area reached higher efficiency (17 %) in the intercropping of Guinea grass with sorghum. After the cut, P. maximum attained 1.40 m of height and its biomass production (3.89 t ha-1) was superior to that of other pasture species. It was concluded that, in ILPF systems, the use of atrazine does not affect its productive performance, when using direct sowing. Sorghum yield is not affected by the intercropping of Guinea grass, brachiaria, and andropogon, and it is an ecologically viable alternative in the implantation or renewal of the grasslands. Key words: pastures, intercropping, sorghum, herbicide, forage grasses.